2004
DOI: 10.1007/s00221-003-1774-0
|View full text |Cite
|
Sign up to set email alerts
|

Endomorphins exit the brain by a saturable efflux system at the basolateral surface of cerebral endothelial cells

Abstract: Endomorphin-1 (EM-1) and endomorphin-2 (EM-2) are two highly selective mu-opiate receptor agonists. We recently demonstrated that EM-1 and EM-2 have a saturable transport system from brain-to-blood in vivo. Since the endothelial cells are the main component of the non-fenestrated microvessels of the blood-brain barrier (BBB), we examined whether these endogenous tetrapeptides have a saturable transport system in cultured cerebral endothelial cells. EM-1 and EM-2 binding and transport were studied in a transwel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
(30 reference statements)
1
10
0
Order By: Relevance
“…In addition to the necessity for enzymic stability, it is widely accepted that peptides must cross the BBB to reach the CNS in an amount sufficient to act on appropriate receptors to exert the desired pharmacological effects (Gentry et al, 1999;Habgood et al, 2000). Recently, EM-1 and EM-2 have been demonstrated to have a saturable efflux system at the BBB (Kastin et al, 2001;Somogyvari-Vigh et al, 2004), which removes the peptides from the CNS, thus limiting brain uptake. Therefore, peptides need to find alternative transcellular pathways to increase their entry into the CNS for their potent biological activity, for example, by passive diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the necessity for enzymic stability, it is widely accepted that peptides must cross the BBB to reach the CNS in an amount sufficient to act on appropriate receptors to exert the desired pharmacological effects (Gentry et al, 1999;Habgood et al, 2000). Recently, EM-1 and EM-2 have been demonstrated to have a saturable efflux system at the BBB (Kastin et al, 2001;Somogyvari-Vigh et al, 2004), which removes the peptides from the CNS, thus limiting brain uptake. Therefore, peptides need to find alternative transcellular pathways to increase their entry into the CNS for their potent biological activity, for example, by passive diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, leucocytes have been also demonstrated to express MaRs, thus allowing to hypothesize that EM-1 could exert multiple analgesic/anti-inflammatory effects in both an autocrine and paracrine fashion (22)(23)(24). Notably, recent evidence demonstrated that EM-1 can actively cross the blood-brain barrier (BBB), thus diffusing into the blood and possibly reaching distant inflamed tissues (4)(5), also affecting the functions of circulating MaR-expressing cells.…”
Section: Discussionmentioning
confidence: 99%
“…from the central nervous system (4)(5). Coherently, EM-l presence has been traced in many peripheral inflamed tissues, where it has proven to significantly decrease sensory neuron firing rate (6)(7) and, most notably, to significantly suppress the release of inflammatory factors from macrophages, which mainly accounts for the development of any algesic reaction occurring in peripheral tissues (6).…”
mentioning
confidence: 99%
“…These transport systems, known as peptide transport system (PTS)-1, PTS-2, PTS-3, and PTS-4, are Na ϩ -independent and show no involvement of metabolic energy. Another transport system that is specific for endomorphins has also been described in the blood-brain barrier (Kastin et al, 2001;Somogyvari-Vigh et al, 2004). A distinct transport system specific for deltorphins, which shows partial Na ϩ dependence but with no evidence of concentrative uptake, has been described in brain microvessels (Fiori et al, 1997).…”
Section: Discussionmentioning
confidence: 99%